Occupational Health and Safety legislative compliance in the construction sites in Windhoek, Namibia - Nghitanwa, Emma Maano; Zungu, Lindiwe I (International Journal of Health, 2017)
Non compliances towards occupational health and safety legislations has been on increase globally which leads to higher incidence of occupational accidents, injuries and diseases. The aim of the study is to determine the presence of occupational hazards in the construction industry and to investigate the occupational health and safety provision and compliance among construction sites in Windhoek. A quantitative, cross-sectional, descriptive design was used to conduct the study. Census sampling was used to include ten construction sites with project running during data collection time and whose site managers agreed to participate in the study. Data was collected in ten construction sites with the site inspection checklist to assess the occupational hazards and OHS compliance in participated construction sites. Data was analysed with SPSS software. The study findings indicated that occupational hazards are prevalent in the construction industry, but there is poor mechanism to control hazards and to prevent hazard exposures. Furthermore, most construction sites are non compliant towards OHS legislations. It is recommended that OHS legislations should be enforced to promote the OHS in the construction industry.